(3eaGgje YGeI, GSJQGJjLjGJg, HjFJg h cjajI GNJjGQ GdCShGb GdOhdjIs - (3aVjd(B, (3aGQSs ((3GdLRGFQ(B:s (3eWHYI GdGNhI GdehSGc(B,s, 2010)
(3YehejGJ Mhd GdJShjb GdOhdj , HYV fXQjGJ GdGSJKeGQ GdeHGTQ GdOhdj h SdhcGdJShjb GdOhdj , eJZjQGJ GdefGN GdJShjb GdOhdj ,fXGe GdeYdheGJ GdOhdjI h HMhK GdJSShjb , ENJjGQ GdGShGb GdOhdjI h CSGdjH GdJhGLO ajgG , YfGUQ GdeRjL GdJShjbj GdOhdj h GSJQGJjLjGJg (B.s
Keywords: (3GdCShGb GdOhdjIs; (3GdJShjbs; (3GdJShjb GdOhdjs